تحقيق المناط في مستجدات النوازل الطبية، دراسة فقهية مقاصدية: (Taḥqīq al-Manāṭ (Investigation of Al-Manat) in the Latest Developments in Medical Calamities: A Purposeful Jurisprudential Study) - خالد بن عبد الله بن علي المزيني (At-Tajdid - Intellectual Refereed Journal, 2025)
This research discusses the challenges related to issuing legal fatwas on medical cases, and because the jurist is not a specialist in medical science, his fatwa depends on the correct news from a trustworthy doctor, who informs him of what helps him to visualize the medical incident well. The research discusses how to conceptualize the medical incident, then this is followed by the initiation In editing the procedures for jurisprudential consideration thereof, by revising the incident, and editing its rank in the hierarchy of legal demands: necessities, needs, and improvements, then considering the appropriate rulings, Since this work is composed of the stages referred to above; The problems related to it are discussed in this research. This research employs the descriptive approach in narrating the sayings and opinions of jurists, and then uses the critical approach in examining the opinions and possibilities proposed to address contemporary medical issues. The researcher draws attention to the importance of taking care to sort the medical cases that fall into the three levels of interests, which are necessities, needs, and improvements, especially this last level. Because problems occur frequently, and there are forms of beautification that resemble some of the forms mentioned in texts and fatwas, but they do not match them, because they are fraught with details that make the ruling on permissibility closer than prohibition, and I mentioned that in the research. Keywords: Fatwas, downloading rulings, realizing the mandate, sick cases, medical rulings, calamities, developments, purposes.